Neurophysiological contributors to advantageous risk-taking: an experimental psychopharmacological investigation. Issue 9 (16th April 2021) - MacCormack, Jennifer K; Armstrong-Carter, Emma; Humphreys, Kathryn L; Muscatell, Keely A
Abstract: The ability to learn from experience is critical for determining when to take risks and when to play it safe. However, we know little about how within-person state changes, such as an individual's degree of neurophysiological arousal, may impact the ability to learn which risks are most likely to fail vs succeed. To test this, we used a randomized, double-blind, placebo-controlled design to pharmacologically manipulate neurophysiological arousal and assess its causal impact on risk-related learning and performance. Eighty-seven adults (45% female, M age = 20.1 ± 1.46 years) took either propranolol ( n = 42), a beta-adrenergic receptor blocker that attenuates sympathetic nervous system–related signaling, or a placebo ( n = 45). Participants then completed the Balloon Emotional Learning Task, a risk-taking task wherein experiential learning is necessary for task success. We found that individuals on propranolol, relative to placebo, earned fewer points on the task, suggesting that they were less effective risk-takers. This effect was mediated by the fact that those on propranolol made less optimal decisions in the final phase of the task on trials with the greatest opportunity for advantageous risk-taking. These findings highlight that neurophysiological arousal supports risk-related learning and, in turn, more advantageous decision-making and optimal behavior under conditions of risk.